Pan-European survey on the implementation of minimally invasive pancreatic surgery with emphasis on cancer. Issue 2 (February 2016) - de Rooij, Thijs; Besselink, Marc G.; Shamali, Awad; Butturini, Giovanni; Busch, Olivier R.; Edwin, Bjørn; Troisi, Roberto; Fernández-Cruz, Laureano; Dagher, Ibrahim; Bassi, Claudio; Abu Hilal, Mohammad; ,
Abstract: Background: Minimally invasive (MI) pancreatic surgery appears to be gaining popularity, but its implementation throughout Europe and the opinions regarding its use in pancreatic cancer patients are unknown. Methods: A 30-question survey was sent between June and December 2014 to pancreatic surgeons of the European Pancreatic Club, European-African Hepato-Pancreato-Biliary Association and 5 European national pancreatic societies. Incomplete responses were excluded. Results: In total, 237 pancreatic surgeons responded. After excluding 34 incomplete responses, 203 responses from 27 European countries were included. 164 (81%) surgeons were employed at a university hospital, 184 (91%) performed advanced MI surgery and 148 (73%) performed MI distal pancreatectomy. MI pancreatoduodenectomy was performed by 42 (21%) surgeons, whereas 9 (4.4%) surgeons had performed more than 10 procedures. Robot-assisted MI pancreatic surgery was performed by 28 (14%) surgeons. 63 (31%) surgeons expected MI distal pancreatectomy for cancer to be inferior to open distal pancreatectomy concerning oncological outcomes. 151 (74%) surgeons expected to benefit from training in MI distal pancreatectomy and 149 (73%) were willing to participate in a randomized trial on this topic. Conclusions: MI distal pancreatectomy is a common procedure, although its use for cancer is still disputed. MI pancreatoduodenectomy is still an uncommon procedure. Specific training and a randomized trial regarding MI pancreatic cancer surgery are welcomed.